Psychic Wounds of Post-Traumatic Stress Disorder camouflaged under the uniform of an SANDF soldier - Sibanda, Sharon; Guse, Tharina; Chigeza, Shingairai (PINS-Psychology in Society, 2022)
The authors explored the lived experiences of traumatisation among active Black military personnel from a psychodynamic (Object Relations) framework. The broad aim of this study was to explore traumatisation and subsequent long-term undiagnosed post-traumatic stress disorder (PTSD) in the presenting behaviour and overall psychological functioning of Black members in the South African National Defence Force (SANDF). N=9 members of the SANDF participated in the study. The study was conducted using a qualitative approach and a phenomenological research design. Data was obtained using individual semi-structured interviews, with IPA as a method of analysis. The findings indicated that participants lived experience of traumatisation is a chronic state of psychic, occupational and relational re-traumatisation. Continuous traumatisation that reactivated past unresolved traumas was characterised by annihilation anxiety, psychic numbing and repression. Phenomenologically overall functional paralysis was evidenced in chronic psychological deterioration, which manifests in irreversible damage to character, with cognitive and relational deficits linked to unresolved long-term traumatisation. These findings highlight a need to incorporate psychotherapeutic models focused on integrative meaning making of psychic distress for adaptive functioning of SANDF members, suffering from long-term undiagnosed PTSD syndrome from pre-integration armed forces combat experiences.